2018
DOI: 10.1186/s12955-018-1039-z
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric brachial plexus injuries (OBPIs): health-related quality of life in affected adults and parents

Abstract: BackgroundObstetric brachial plexus injuries (OBPIs) are rare but can have significant implications for those affected, their caregivers and the health system. Symptoms can range from restricted movement to complete paralysis of the arm. We investigated health-related quality of life in adults with OBPIs and parents of children with permanent OBPIs, compared these with population norms, and investigated whether certain socio-demographic or clinical factors were associated with the quality of life in these coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…Utility scores and Quality Adjusted Life Years (QALYs). The mean utility scores for adults (aged 18 years and over) with OBPIs and parents of children with OBPIs was extracted from our previously published study [2]. The total affected adult QALYs per model year were calculated using the mean utility score for adults with OBPIs, the number of individuals with OBPIs and the number of years they would have been adults for by the end of the model's time horizon (30 years).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Utility scores and Quality Adjusted Life Years (QALYs). The mean utility scores for adults (aged 18 years and over) with OBPIs and parents of children with OBPIs was extracted from our previously published study [2]. The total affected adult QALYs per model year were calculated using the mean utility score for adults with OBPIs, the number of individuals with OBPIs and the number of years they would have been adults for by the end of the model's time horizon (30 years).…”
Section: Plos Onementioning
confidence: 99%
“…Shoulder dystocia is an obstetric emergency and occurs when the anterior shoulder of a baby is impacted against the mother's pelvic bone during birth [1]. Mismanagement of this childbirth emergency, such as excessive traction on a baby's neck, can cause permanent injuries to the nerves in the neck (known as obstetric brachial plexus injuries (OBPIs)) resulting in long term morbidity and loss of quality of life [2]. Although permanent OBPIs are relatively rare, with incidence rates of 0.192 per 1,000 births in the UK [3] and 0.11-0.22 per 1,000 births in the US [4], these injuries are important sources of litigation and therefore impact the wider health system as well as the affected individuals and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Dados da literatura mostram sequelas em 20 a 30% dos pacientes acometidos, o pode comprometer a qualidade de vida desses pacientes, e trazer implicações significativas para os familiares e para o sistema de saúde (Yau, 2018;Smith, 2018 (Borges, 2016).…”
Section: Paralisia Do Plexo Braquial Neonatal: Uma Discussão à Luz Daunclassified
“…Yau, 2018). O manejo adequado e precoce dos casos pode minimizar as potenciais complicações.O objetivo desse trabalho foi realizar uma revisão sobre a Paralisia do Plexo Braquial Neonatal e, além disso, apresentar uma proposta de atendimento para esses pacientes.…”
unclassified
“…OBPI in adults causes difficulties in completing daily tasks and therefore the quality of their life. 32 The long-term effects of OBPI include a high propensity for pain exacerbation and worsening ability to move the shoulder with advancing age. 33 These investigators also reported that many of these patients had developed arthritis in the joints and spine.…”
Section: Introductionmentioning
confidence: 99%